Cellular Plasticity in Gut and Liver Regeneration - Minwook Kim; Yoojeong Park; You Sun Kim; Sungjin Ko (Gut and Liver)
The intestine and liver share a unique regenerative property that sets them apart from other mammalian visceral organs. The intestinal epithelium exhibits rapid renewal, making it one of the fastest renewing tissues in humans. Under physiological conditions, intestinal stem cells within each intestinal crypt continuously differentiate into the different types of intestinal epithelial cells to maintain intestinal homeostasis. However, when exposed to tissue damage or stressful conditions such as inflammation, intestinal epithelial cells in the gastrointestinal tract exhibit plasticity, allowing fully differentiated cells to regain their stem cell properties. Likewise, hepatic epithelial cells possess a remarkable regenerative capacity to restore lost liver mass through proliferation-mediated liver regeneration. When the proliferation-mediated regenerative capacity is impaired, hepatocytes and biliary epithelial cells (BECs) can undergo plasticity-mediated regeneration and replenish each other. The transition of mammalian liver progenitor cells to hepatocytes/BECs can be observed under tightly controlled experimental conditions such as severe hepatocyte injury accompanied by the loss of regenerative capacity. In this review, we will discuss the mechanism by which cellular plasticity contributes to the regeneration process and the potential therapeutic implications of understanding and harnessing cellular plasticity in the gut and liver.